Caryocar brasiliense Camb. fruit peel butanolic fraction induces antiproliferative effects against murine melanoma cell line - Jéssica Nayara Basílio Silva; Victor Hugo Dantas Guimarães; Barbhara Mota Marinho; Amanda Souto Machado; Amanda Rodrigues Santos; Ludmilla Regina de Souza David; Geraldo Aclécio Melo; Alfredo Maurício Batista de Paula; Sérgio Henrique Sousa Santos (Elsevier, 2022)
Background: Cutaneous malignant melanoma is a skin cancer type highly resistant to standard cancer therapies. Natural compounds have been reported as important sources for the creation of new drugs for cancer treatment. Caryocar brasiliense Camb., popularly known as Pequi, is often used in Brazilian folk medicine, with anticancer effects reported. Objectives: The present study evaluated the antiproliferative activity of the crude extract butanolic fraction of the C. brasiliense Camb. peel on the B16F10 cell linage Method: C. brasiliense peel fraction was analyzed by Gas Chromatography coupled to massa spectra, and its biological effects were evaluated on the melanoma cell line B16F10. Results: The chromatography analysis of the butanolic fraction of the C. brasiliense peel fraction identified a majority presence of gallic acid and sarothrin compounds. These compounds might have been responsible for an antiproliferative effect on B16F10, with the inhibitory concentration (IC50) equal to 390.9 µg/mL (24 h) and 226.4 µg/mL (48 h) after treatments. Our results revealed that cell death assay via bromide and acridine orange tests indicated an increase in cell death observed after 24 h treatment with the pequi fraction at 250 μg/mL (p < 0.05) and 500 μg/mL (p < 0.01). In addition, a significant increase in cell death at 250 μg/mL (p < 0.01) and 500 μg/mL (p < 0.0001) occurred after 48 h. Furthermore, a significant reduction in migratory activity in cells treated at 250 μg/mL (p < 0.05) and 500 μg/mL (p < 0.01) occurred and was enhanced by the 48 h treatment (p < 0.001). Conclusions: The present study is the first to demonstrate the use of ''Pequi'' residual by product as a potential reservoir of bioactive compounds with antiproliferative activity on B16F10 melanoma cells.